Farm Size and Productivity Relationship in Dryland Agriculture in Nagauh. District (Rajasthan) - Vyas, D L (Annals of Arid Zone, 2025)
Farm-size productivity relationship in dryland agriculture in Nagaur district of Rajasthan State was examined for three successive years (1977-78 to 1979-80) by empolying correlation and regression methods. Return to scale in dry land agriculture was positive but predominantly of very low order. There is a scope for soil conservation and irrigation facilities for further enhancing the per hectare productivity particularly, on small farms.